Manajemen Konflik Pernikahan Campuran (Studi Kasus pada Suami Istri Etnis Jawa dan Madura) - Su’ada, Hanif Nur; Ash-Shiddiq, R. Muhammad Ikhwanul Fitrah; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study purpose to find out how married couples of different tribes resolve conflicts that occur in their marriages. This research is qualitative using case study types, data collection techniques using interviews, observations, and documentation studies. The informants in this study amounted to 3 married couples who came from different tribes or ethnicities. The results of the study obtained were differences in background and ethnicity did not greatly affect the harmony of the marriage relationship of the three couples, although there were often conflicts. In resolving the conflict is not so difficult because it is based on feelings of affection towards fellow partners. Two of them solve problems by using the type of collaborating, and the rest using the type of accommodating.